2018
DOI: 10.1159/000488913
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Combined Degeneration: A Retrospective Study of 68 Cases with Short-Term Follow-Up

Abstract: Purpose: The study aimed to analyze the clinical characteristics, laboratory test results, neuroimaging findings, and outcomes in patients diagnosed with subacute combined degeneration (SCD). Materials and Methods: A total of 68 patients with SCD who had been appropriately treated for no less than 6 months were included in our study. Histories, results of routine blood tests, biochemical indices, serum vitamin B12 levels, and spinal magnetic resonance imaging (MRI) findings from the patients were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 24 publications
4
45
0
Order By: Relevance
“…However, to the best of our knowledge, none of these studies have reported a relationship between the evolution of dynamic neuroimaging and clinical manifestations in a patient with N 2 O-induced SCD. Treatment is frequently discontinued by individuals who abuse N 2 O following improvement in the neurological symptoms [3]. Moreover, guidelines for treatment duration have not been established for patients with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, none of these studies have reported a relationship between the evolution of dynamic neuroimaging and clinical manifestations in a patient with N 2 O-induced SCD. Treatment is frequently discontinued by individuals who abuse N 2 O following improvement in the neurological symptoms [3]. Moreover, guidelines for treatment duration have not been established for patients with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to many other etiologies of SCD, N2O-mediated inactivation of B12 is not consistently tied to hematologic symptoms (e.g. macrocytic anemias) as might be expected in other causes of SCD such as pernicious anemia [ 11 , 12 ]. In both anesthetic and recreational use, worsened clinical manifestations are not expected to be associated with anemia, low levels of serum vitamin B12, or MRI abnormalities in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…In both anesthetic and recreational use, worsened clinical manifestations are not expected to be associated with anemia, low levels of serum vitamin B12, or MRI abnormalities in the spinal cord. The age of onset and disease course are important factors in evaluating the short-term prognosis of patients with SCD [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations